Rapid Fluvio-Thermal Erosion of a Yedoma Permafrost Cliff in the Lena River Delta - Fuchs, Matthias; Nitze, Ingmar; Strauss, Jens; Günther, Frank; Wetterich, Sebastian; Kizyakov, Alexander; Fritz, Michael; Opel, Thomas; Grigoriev, Mikhail N.; Maksimov, Georgii T.; Grosse, Guido (Frontiers in Earth Science, 2020)
The degradation of ice-rich permafrost deposits has the potential to release large amounts of previously freeze-locked carbon (C) and nitrogen (N) with local implications, such as affecting riverine and near-shore ecosystems, but also global impacts such as the release of greenhouse gases into the atmosphere. Here, we study the rapid erosion of the up to 27.7 m high and 1,660 m long Sobo-Sise yedoma cliff in the Lena River Delta using a remote sensing-based time-series analysis covering 53 years and calculate the mean annual sediment as well as C and N release into the Lena River. We find that the Sobo-Sise yedoma cliff, which exposes ice-rich late Pleistocene to Holocene deposits, had a mean long-term (1965–2018) erosion rate of 9.1 m yr–1 with locally and temporally varying rates of up to 22.3 m yr–1. These rates are among the highest measured erosion rates for permafrost coastal and river shoreline stretches. The fluvio-thermal erosion led to the release of substantial amounts of C (soil organic carbon and dissolved organic carbon) and N to the river system. On average, currently at least 5.2 × 106 kg organic C and 0.4 × 106 kg N were eroded annually (2015–2018) into the Lena River. The observed sediment and organic matter erosion was persistent over the observation period also due to the specific configuration of river flow direction and cliff shore orientation. Our observations highlight the importance to further study rapid fluvio-thermal erosion processes in the permafrost region, also because our study shows increasing erosion rates at Sobo-Sise Cliff in the most recent investigated time periods. The organic C and N transport from land to river and eventually to the Arctic Ocean from this and similar settings may have severe implications on the biogeochemistry and ecology of the near-shore zone of the Laptev Sea as well as for turnover and rapid release of old C and N to the atmosphere.